Carbon nanofibers addition on transport and superconducting properties of bulk YBa2Cu3O7−δ material prepared via co-precipitation - Khalid, Nurul Auni; Awang Kechik, Mohd Mustafa; Baharuddin, Nur Atikah; Chen, Soo Kien; Baqiah, Hussein; Lim, Kean Pah; Shaari, Abdul Halim; Talib, Zainal Abidin; Hashim @ Ismail, Azhan; Murakami, Masato; Miryala, Muralidhar (Springer, 2020)
The effects of carbon nanofibers addition on transport and superconducting properties of YBa2Cu3O7−δ (Y-123) superconductor were studied. Y-123 was prepared using co-precipitation method for good quality bulk of high temperature superconducting material. Carbon nanofibers with 0.2–0.8 wt% were added into Y-123 superconductors. The samples were characterized using electrical resistance measurement for critical temperature (Tc) and critical current density (Jc), powder X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray analysis. Most of the samples indicated a dominant Y-123 phase of an orthorhombic structure with a minor phase of BaCO3 and Y-124. Onset critical temperature was found to decrease from 90.5 to 80 K with increasing of carbon nanofibers concentration. The Jc for pure sample is 11 A/cm2 at 30 K while the Jc of sample with 0.4 wt% carbon nanofibers is 830 A/cm2 at 30 K. Introduction of carbon nanofibers enhanced Jc significantly. However, further addition of carbon nanofibers in Y-123 superconductor caused degradation in Jc.